2007
DOI: 10.1074/jbc.m700078200
|View full text |Cite
|
Sign up to set email alerts
|

Kruppel-like Factor 4 Regulates Endothelial Inflammation

Abstract: The vascular endothelium plays a critical role in vascular homeostasis. Inflammatory cytokines and non-laminar blood flow induce endothelial dysfunction and confer a pro-adhesive and pro-thrombotic phenotype. Therefore, identification of factors that mediate the effects of these stimuli on endothelial function is of considerable interest. Kruppel-like factor 4 expression has been documented in endothelial cells, but a function has not been described. In this communication we describe the expression in vitro an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
228
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 337 publications
(252 citation statements)
references
References 86 publications
13
228
2
1
Order By: Relevance
“…This suggests that KLF2 and KLF4 act partially redundant in ECs. This is also supported by a recent study that previously reported induction of established KLF2 targets by KLF4 in ECs (27). Moreover, another study showed a compensatory upregulation of KLF4 upon deletion of one KLF2 allele, which has been suggested to account for the absent endothelial phenotype upon partial KLF2 loss (39).…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…This suggests that KLF2 and KLF4 act partially redundant in ECs. This is also supported by a recent study that previously reported induction of established KLF2 targets by KLF4 in ECs (27). Moreover, another study showed a compensatory upregulation of KLF4 upon deletion of one KLF2 allele, which has been suggested to account for the absent endothelial phenotype upon partial KLF2 loss (39).…”
Section: Discussionsupporting
confidence: 74%
“…Thus, our data not only prove that KLF4 is located downstream of Erk5 but also demonstrate that it indeed represents a functionally relevant mediator of Erk5-dependent gene expression in ECs. In agreement with that, KLF4 has previously been identified in a microarray study for flow-activated genes (28) and is known to suppress proinflammatory gene expression in ECs (27). It should be noted, however, that consistent with a study in Erk5-deficient mouse embryonic fibroblasts (26), we additionally identified KLF2 as major factor induced by active MEK5D.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations